Seismic Imaging of the Alaska Subduction Zone: Implications for Slab Geometry and Volcanism. (21st November 2018) - Martin‐Short, Robert; Allen, Richard; Bastow, Ian D.; Porritt, Robert W.; Miller, Meghan S.
Abstract: Alaska has been a site of subduction and terrane accretion since the mid‐Jurassic. The area features abundant seismicity, active volcanism, rapid uplift, and broad intraplate deformation, all associated with subduction of the Pacific plate beneath North America. The juxtaposition of a slab edge with subducted, overthickened crust of the Yakutat terrane beneath central Alaska is associated with many enigmatic volcanic features. The causes of the Denali Volcanic Gap, a 400‐km‐long zone of volcanic quiescence west of the slab edge, are debated. Furthermore, the Wrangell Volcanic Field, southeast of the volcanic gap, also has an unexplained relationship with subduction. To address these issues, we present a joint ambient noise, earthquake‐based surface wave, and P ‐ S receiver function tomography model of Alaska, along with a teleseismic S wave velocity model. We compare the crust and mantle structure between the volcanic and nonvolcanic regions, across the eastern edge of the slab and between models. Low crustal velocities correspond to sedimentary basins, and several terrane boundaries are marked by changes in Moho depth. The continental lithosphere directly beneath the Denali Volcanic Gap is thicker than in the adjacent volcanic region. We suggest that shallow subduction here has cooled the mantle wedge, allowing the formation of thick lithosphere by the prevention of hot asthenosphere from reaching depths where it can interact with fluids released from the slab and promote volcanism. There is no evidence for subducted material east of the edge of the Yakutat terrane, implying the Wrangell Volcanic Field formed directly above a slab edge. Plain Language Summary: We present new images of the Alaskan subduction zone that reveal the three‐dimensional structure of the upper mantle and crust. Our study leverages data from a new array of high‐quality seismometers, the Transportable Array, which has been deployed across the entire state. We combine multiple geophysical techniques with complementary strengths to examine the upper 150 km over a wider geographic area than has previously been imaged. This enables us to observe major changes in crustal thickness across Alaska, map the eastern edge of the subducted Yakutat‐Pacific plate, and note that the enigmatic Wrangell Volcanoes lie directly above this edge, which may help to explain their unusual features. We also observe significant differences in the mantle structure beneath a volcanic region, the Aleutian Arc, and an adjacent zone of volcanic quiescence. We infer that shallow‐angle subduction beneath this region has cooled the mantle here and thus limits the production of magma for volcanoes. Key Points: We use receiver functions, ambient noise, earthquake‐based surface wave, and teleseismic body wave tomography to image the Alaskan subsurface Shallow subduction below the Denali Volcanic Gap prevents asthenospheric flow into zones of slab fluid release, suppressing volcanism here The edge of the subducted Yakutat terrane delineates the easternmost extent of subduction; the Wrangell Volcanic Field lies above this edge